2008
DOI: 10.1038/ncb1678
|View full text |Cite
|
Sign up to set email alerts
|

Wingless secretion requires endosome-to-Golgi retrieval of Wntless/Evi/Sprinter by the retromer complex

Abstract: The glycolipoproteins of the Wnt family raise interesting trafficking issues, especially with respect to spreading within tissues. Recently, the retromer complex has been suggested to participate in packaging Wnts into long-range transport vehicles. Our analysis of a Drosophila mutant in Vps35 show that, instead, the retromer complex is required for efficient progression of Wingless (a Drosophila Wnt) through the secretory pathway. Indeed expression of senseless, a short-range target gene, is lost in Vps35-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
249
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(269 citation statements)
references
References 23 publications
15
249
3
2
Order By: Relevance
“…Wls (also known as Evi or Sprinter in flies and MIG-14 in Caenorhabditis elegans) is an integral membrane protein found in the Golgi, plasma membrane, and endosomes (Banziger et al 2006;Belenkaya et al 2008;Franch-Marro et al 2008b;Port et al 2008;Yang et al 2008). Retromer is a multiprotein complex that shuttles cargo from endosomes to the trans-Golgi (Seaman 2005).…”
Section: Getting Out and About-wnt Secretion And Transportmentioning
confidence: 99%
“…Wls (also known as Evi or Sprinter in flies and MIG-14 in Caenorhabditis elegans) is an integral membrane protein found in the Golgi, plasma membrane, and endosomes (Banziger et al 2006;Belenkaya et al 2008;Franch-Marro et al 2008b;Port et al 2008;Yang et al 2008). Retromer is a multiprotein complex that shuttles cargo from endosomes to the trans-Golgi (Seaman 2005).…”
Section: Getting Out and About-wnt Secretion And Transportmentioning
confidence: 99%
“…In the Wnt secretory pathway, this lipid modification is important for the interaction between Wnt proteins and the conserved transmembrane protein Evi (Wls, GPR177), which shuttles lipid‐modified Wnt proteins to the plasma membrane and onto exovesicles (Bänziger et al , 2006; Bartscherer et al , 2006; Goodman et al , 2006; Gross et al , 2012; Herr & Basler, 2012). Evi is then recycled via the retromer complex back to the Golgi and ER (Coudreuse, 2006; Belenkaya et al , 2008; Franch‐Marro et al , 2008; Pan et al , 2008; Port et al , 2008; Yang et al , 2008; Yu et al , 2014). The levels of both Wnt and Evi proteins are often aberrantly regulated in cancer (Augustin et al , 2012; Voloshanenko et al , 2013; Stewart et al , 2015), which contributes to high Wnt activity during tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Retromer was originally identified as essential in yeast for the proper retrieval of the vacuolar hydrolase receptor Vps10 from late endosomes back to the trans-Golgi network (Horazdovsky et al, 1997;Seaman et al, 1997) and was later shown to function in an analogous manner in mammalian cells in regard to retrieval of the cation-independent mannose-6-phosphate receptor (Arighi et al, 2004;Seaman, 2004). Since then, retromer has been implicated in a broad range of protein-sorting pathways and has most recently been shown to be required for the maintenance of proper Wnt secretion in the development of both Caenorhabditis elegans and Drosophila melanogaster (Belenkaya et al, 2008;Franch-Marro et al, 2008;Pan et al, 2008;Port et al, 2008;Yang et al, 2008), underscoring its importance in retrograde transport. In yeast retromer is composed of five proteins that assemble into two subcomplexes: Vps5 and Vps17 (Snx1/ Snx2 and Snx5/Snx6 in mammals) and Vps26, Vps29, and Vps35 (and the homologous proteins in metazoans; Seaman et al, 1998;Haft et al, 2000;Wassmer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%